Limitations of the Plasmid-Based Cas9-Zinc Finger Fusion System for Homology-Directed Knock-In in Chinese Hamster Ovary Cells - Kim, Dongwoo; Lee, Jae Seong (Biotechnology and bioprocess engineering, 2023)
The clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) system has been used for the insertion of large transgenes into Chinese hamster ovary cells via co-transfection of a Cas9/guide RNA expression vector and donor plasmid. The Cas9 protein includes nuclear localization sequences that are used as peptide tags for the import of Cas9 into the nucleus. However, the import of a donor plasmid into the nucleus is passive because of the absence of such localization signals; thus, the delivery of Cas9 and the donor plasmid is not synchronized, resulting in low knock-in (KI) efficiency. Here, we modified the Cas9 expression vector expressing a Cas9 protein fused to a zinc finger (ZF) domain, Cas9-ZF, to expedite the translocation of the donor plasmid into the nucleus and the co-localization of the donor plasmid with a CRISPR/Cas9-mediated DNA double-strand break site by tethering Cas9-ZF and the donor plasmid. Compared to the typical donor plasmid and wild-type Cas9, the donor plasmid harboring the ZF-binding motif showed increased homology-mediated KI efficiency, while the engineered Cas9 protein showed decreased expression and gene-editing efficiency. Moreover, the pair of Cas9-ZF and the donor plasmid with the ZF motif did not improve KI efficiency, but rather negated the positive effect of the donor plasmid with the ZF motif. This study demonstrates the importance of the transport of donor plasmids and the limitations of using the plasmid-based Cas9-ZF fusion system to improve KI efficiency.